Evaluation of dispersed effect based on social force-based vehicle model and emotional infection model: a data simulation approach. (2018) - Lu, Ling; Zhuang, Hongwei; Gao, Zhiqiang
Tear gas bomb is often used by police to disperse people when dealing with illegal gatherings. When people are strongly stimulated, they will produce different reactions, one of which is to run away to avoid stimuli. The data of trajectories is a data stream, which will vary depending on the different forces. In this paper, the major stimulants are strong sound and smoke which come from exploding tear gas bomb. Combining the psychology of the crowd, characteristics of reaction behaviour and environment, the psychological dispersed force and physiological dispersed force are analysed. The model is established combined with the social force model of traffic flow. Comparing the data flow between the experimental and simulated experiments, the error between the simulated and measured value is less than 6%. The built-up dispersed model can basically reflect the actual dispersal effect of exploding tear gas bomb.